The Effect of Capital Structure, Firm Size, and Institutional Ownership on Firm Value with Profitability as a Mediating Variable In Pharmaceutical Companies Listed on the Indonesia Stock Exchange in 2020-2023 - Sohabat Nasuha; Yuliusman, Yuliusman; Ratih Kusumastuti (CV. AFDIFAL MAJU BERKAH, 2024)
This research aimed to examine the impact of capital structure, firm size, and institutional ownership on firm value, with profitability acting as a mediating variable. The study utilized secondary data from the annual reports and financial statements of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. Using Smart-PLS software, the results revealed that capital structure negatively affects profitability, while firm size and institutional ownership do not influence profitability. Additionally, capital structure, firm size, and institutional ownership were found to have no effect on firm value. However, profitability positively impacts firm value, yet when mediated by profitability, capital structure, firm size, and institutional ownership do not affect firm value.